Alishewanella solinquinati sp nov., isolated from soil contaminated with textile dyes - Kolekar, Yogesh M.; Pawar, Shrikant P.; Adav, Sunil S.; Zheng, Liu-Qiang; Li, Wen-Jun; Shouche, Yogesh S.; Dastager, Syed Gulam; Kodam, Kisan M. (Current Microbiology, 2013)
A novel Gram-negative, motile, rod-shaped, facultative anaerobic bacterial strain, KMK6(T), was isolated from soil contaminated with textile dyes from an industrial estate located at Ichalkaranji, Maharashtra, India, and its taxonomical position was established by using a polyphasic approach. The major cellular fatty acids included C-17:1 omega 8c, summed feature 3 (C-16:1 omega 7c and/or iso-C-15:0 2-OH), C-17:0, C-16:0,C- and C-18:1 omega 7c. The DNA G+C content of strain KMK6(T) was 48.8 mol %. 16S rRNA gene sequence analysis confirmed its placement in the genus Alishewanella, and exhibited sequence similarity levels of below 97 % to the type strains of validly published Alishewanella species. On the basis of genotypic and phenotypic evidence, strains KMK6(T) is considered to be a novel species of the genus Alishewanella, for which we propose that strain KMK6(T) (=NCIM 5295(T) =BCRC 17848(T)) is assigned to a novel species, Alishewanella solinquinati sp. nov.

Arthrobacter enclensis sp. nov., isolated from sediment sample - Dastager, Syed Gulam; Qin, Liu; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Lee, Jae-Chan; Li, Wen-Jun (Archives of Microbiology, 2014)
A novel bacterial strain designated as NIO-1008(T) was isolated from marine sediments sample in Chorao Island India. Cells of the strains were gram positive and non-motile, displayed a rod-coccus life cycle and formed cream to light grey colonies on nutrient agar. Strain NIO-1008(T) had the chemotaxonomic markers that were consistent for classification in the genus Arthrobacter, i.e. MK-9(H-2) (50.3 %), as the major menaquinone, and the minor amount of MK-7 (H-2-27.5 %), MK-8 (H-4-11.6 %) and MK-8 (H-2-10.4 %). anteiso-C-15:0, iso-C-15:0, iso-C-16:0 and C-15:0 were the predominant fatty acids. Galactose, glucose and rhamnose are the cell-wall sugars, and DNA G+C content was 61.3 mol%. Phylogenetic analysis, based on 16S rRNA gene sequencing, showed that the strains were most similar to Arthrobacter equi IMMIB L-1606(T), Arthrobacter chlorophenolicus DSM 12829(T), Arthrobacter defluvii KCTC 19209(T) and Arthrobacter niigatensis CCTCC AB 206012(T) with 98.5, 98.4, 98.0 and 97.8 %, respectively, and formed a separate lineage. Combined phenotypic data and DNA-DNA hybridization data supported the conclusion that strains NIO-1008(T) represent a novel species within the genus Arthrobacter, for which the name Arthrobacter enclensis sp. nov., is proposed. The type strain is NIO-1008(T) = (NCIM 5488(T) = DSM 25279(T)).
Keywords: Arthrobacter; Chorao Island; Marine sediment; Polyphasic

Arthrobacter enclensis sp. nov., isolated from sediment sample (vol 196, pg 775, 2014) - Dastager, Syed Gulam; Liu, Qing; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Lee, Jae-Chan; Li, Wen-Jun (Archives of Microbiology, 2014)

Kocuria indica sp nov., isolated from a sediment sample - Dastager, Syed Gulam; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Lee, Jae-Chan; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2014)
An actinobacterial strain was isolated from a sediment sample from Chorao Island, in Goa province, India, and subjected to a taxonomic investigation. The isolate, designated NIO-1021(T), was a Gram-stain positive, aerobic, non-motile and coccoid. Strain NIO-1021(T) was identified as a member of the genus Kocuria by a polyphasic approach. Strain NIO-1021(T) could be differentiated from other members of the genus Kocuria on the basis of physiology and 16S rRNA gene sequence analysis. The 16S rRNA gene sequence similarity of strain NIO-1021(T) to the most closely related species, Kocuria marina KCTC 9943(T), was 98.6% with 19 nt differences). Furthermore, DNA-DNA hybridization analysis revealed that the novel strain had lower relatedness with the type strains of other members of the genus Kocuria. The strain formed a monophyletic clade with K. marina with 100% bootstrap values. The major phospholipids were phosphatidylglycerol, diphosphatidylglycerol and two unidentified lipids. The predominant menaquinone was MK-7(H-2). The major fatty acids were anteiso-C-15:0, iso-C-(16:0) and anteiso-C-17:0. The DNA G+C content of strain NIO-1021(T) was 60.5 mol%. Chemotaxonomic and phylogenetic properties of the strain were consistent with its classification as representing a member of the genus Kocuria. On the basis of phenotypic, chemotypic and molecular characteristics, strain NIO-1021(T) is considered to represent a novel species of the genus Kocuria, for which the name Kocuria indica sp. nov. is proposed, with strain NIO-1021(T) (=NCIM 5455(T)=DSM 25126(T)=CCTCC AA 209050(T)) as the type strain.

Roseovarius azorensis sp nov., isolated from seawater at espalamaca, azores - Rajasabapathy, Raju; Mohandass, Chellandi; Dastager, Syed Gulam; Liu, Qing; Thi-Nhan Khieu; Chu Ky Son; Li, Wen-Jun; Colaco, Ana (Antonie van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A Gram-negative, motile, non-spore forming, rod shaped aerobic bacterium, designated strain SSW084(T), was isolated from a surface seawater sample collected at Espalamaca (38A degrees 33'N; 28A degrees 39'W), Azores. Growth was found to occur from 15 to 40 A degrees C (optimum 30 A degrees C), at pH 7.0-9.0 (optimum pH 7.0) and with 25-100 % seawater or 0.5-7.0 % NaCl in the presence of Mg2+ and Ca2+; no growth was found with NaCl alone. Colonies on seawater nutrient agar were observed to be punctiform, white, convex, circular, smooth, and translucent. Strain SSW084(T) did not grow on Zobell marine agar and tryptic soy agar even when seawater supplemented. The major respiratory quinone was found to be Q-10 and the G + C content was determined to be 61.9 mol%. Phylogenetic analysis based on the 16S rRNA gene sequence indicated that strain SSW084(T) belongs to the genus Roseovarius and that its closest neighbours are Roseovarius tolerans EL-172(T), Roseovarius mucosus DFL-24(T) and Roseovarius lutimaris 112(T) with 95.7, 95.4 and 95.3 % sequence similarity respectively. The remaining species of Roseovarius showed < 95 % similarity. The polar lipids of strain SSW084(T) were determined to be phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylglycerol, phosphatidylcholine, an unidentified lipid and one unidentified aminolipid. The major fatty acids identified were identified as C-18:1 omega 7c (52.5 %) and C-16:0 (13.8 %). On the basis of phenotypic, molecular and chemotaxonomic characteristics, strain SSW084(T) is considered to represent a novel species of the genus Roseovarius, for which Roseovarius azorensis sp. nov is proposed. The type strain is SSW084(T) (=KCTC 32421(T) = MTCC 11812(T)).
Keywords: Espalamaca; Polyphasic taxonomy; Roseovarius azorensis sp nov; Seawater

Citreicella manganoxidans sp nov., a novel manganese oxidizing bacterium isolated from a shallow water hydrothermal vent in Espalamaca (Azores) - Rajasabapathy, Raju; Mohandass, Chellandi; Dastager, Syed Gulam; Liu, Qing; Li, Wen-Jun; Colaco, Ana (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A Gram-stain negative, non-motile, non-spore forming, aerobic and rod or narrow lemon-shaped bacterial strain, VSW210(T), was isolated from surface seawater in a shallow water hydrothermal vent region in Espalamaca (Azores). Strain VSW210(T) was found to grow optimally at 30 A degrees C, at pH 7 and in the presence of 2-6 % (w/v) NaCl. A neighbour-joining phylogenetic tree based on 16S rRNA gene sequences revealed that strain VSW210(T) clusters with the type strain Citreicella marina CK-I3-6(T) (sequence similarity value of 99.6 %), but DNA-DNA hybridization showed DNA-DNA relatedness between the strain VSW210(T) and C. marina CK-I3-6(T) to be 55.8 +/- A 3.2 %. The DNA G+C content of strain VSW210(T) was determined to be 67.4 mol%. The cellular fatty acid profiles of strain VSW210(T) was found to contain C-18:1 omega 7c (80.1 %) and C-16:0 (9.2 %). The major polar lipids in strain VSW210(T) were identified as phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol and an unidentified phospholipid. Strain VSW210(T) was found to be able to oxidize soluble Mn(II) to insoluble MnO2, which was confirmed with LBB staining. Differential phenotypic properties and genetic uniqueness revealed that this strain VSW210(T) is distinguishable from other species of the genus Citreicella. On the basis of the data presented, strain VSW210(T) is considered to represent a novel species of the genus Citreicella, for which the name Citreicella manganoxidans sp. nov. is proposed. The type strain is VSW210(T) (=KCTC 32497(T) = MCC 2286(T)).
Keywords: Azores; Citreicella manganoxidans sp nov; Hydrothermal vent; Polyphasic taxonomy; Seawater

Exiguobacterium enclense sp nov., isolated from sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Thorat, Meghana N.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive bacterium, designated strain NIO-1109(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. Phenotypic and chemotaxonomic characteristics and data from phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1109(T) was related to the genus Exiguobacterium. Strain NIO-1109(T) exhibited >98.0% 16S rRNA gene sequence similarity with respect to Exiguobacterium indicum HHS 31(T) (99.5%) and Exiguobacterium acetylicum NCIMB 9889(T) (99.1 %); the type strains of other species showed <98% similarity. Levels of DNA DNA relatedness between strain NIO-1109(T) and E. acetylicum DSM 20416(T) and E indicum LMG 23471(T) were less than 70% (33.0 +/- 2.0 and 37 +/- 32%, respectively). Strain NIO-1109(T) also differed from these two closely related species in a number of phenotypic traits. Based on phenotypic, chemotaxonomic and phylogenetic data, strain NIO-1109(T) is considered to represent a novel species of the genus Exiguobacterium, for which the name Exiguobacterium enclense sp. nov. is proposed. The type strain is NIO-1109(T) (=NCIM 5457(T)= DSM 25128(T)=CCTCC AB 2011124(T)).

Nioella nitratireducens gen. nov., sp nov., a novel member of the family Rhodobacteraceae isolated from Azorean Island - Rajasabapathy, Raju; Mohandass, Chellandi; Yoon, Jung-Hoon; Dastager, Syed Gulam; Liu, Qing; Khieu, Thi-Nhan; Son, Chu Ky; Li, Wen-Jun; Colaco, Ana (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel Gram-negative, non-spore forming, rod-shaped aerobic bacterium, designated SSW136(T), was isolated from a surface seawater sample collected at Espalamaca (in Faial Island), Azores. Growth was found to occur from 10 to 37 A degrees C, pH 6.0-8.0, and with 2-11 % of NaCl. 16S rRNA gene sequence indicated that the strain SSW136(T) belongs to the family Rhodobacteraceae. Strain SSW136(T) exhibited 96.3, 95.9, 95.7 and 95.5 sequence similarity to the type strains Oceanicola litoreus M-M22(T), Roseovarius aestuarii SMK-122(T), Marivita geojedonensis DPG-138(T), and Pseudoruegeria aquimaris SW-255(T) respectively. Neighbour-joining and maximum-parsimony phylogenetic trees based on 16S rRNA gene sequences revealed that strain SSW136(T) was affiliated to the family Rhodobacteraceae and formed a separate branch. The G+C content was 63.5 mol%. The major respiratory quinone was found to be Q-10. The polar lipids of strain SSW136(T) consisted of phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, two unidentified aminolipids and three unidentified phospholipids. The major fatty acids were C-18:1 omega 7c (46.5 %), Cyclo-C-19:0 omega 8c (16.0 %) and C-16:0 (12.8 %). On the basis of the morphological, genotypic, chemotaxonomic characteristics and low DNA-DNA relatedness, strain SSW136(T) is proposed to represent a novel genus and novel species, Nioella nitratireducens gen. nov., sp. nov., in the family Rhodobacteraceae. The type strain is SSW136(T) (=KCTC 32417(T) = NCIM 5499(T)).
Keywords: Espalamaca; Nioella nitratireducens; Novel genus and species; Polyphasic taxonomy; Seawater

Nonomuraea indica sp nov., novel actinomycetes isolated from lime-stone open pit mine, India - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Li, Jie; Nie, Guo-Xing; Tang, Shu-Kun; Al Ruwaili, Jamal; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (Journal of Antibiotics, 2015)
A Gram-positive, aerobic, nonmotile actinomycete strain designated DRQ-2(T) was isolated from the soil sample collected from limestone open pit mine from the Gulbarga region, Karnataka province, India. Strain DRQ-2(T) was identified as a member of the genus Nonomuraea by a polyphasic approach. Strain DRQ-2(T) could be differentiated from other members of the genus Nonomuraea on the basis of physiology and 16S rRNA gene sequence analysis. The 16S rRNA gene sequence similarity of strain DRQ-2(T) showed highest sequence similarity to Nonomuraea muscovyensis DSM 45913(T) (99.1%), N. salmonea DSM 43678(T) (98.2%) and N. maheshkhaliensis JCM 13929(T) with 98.0%, respectively. Chemotaxonomic properties showing predominant menaquinones of MK-9 (H-4), MK-9(H-2) and MK-9(H-6), major polar lipids comprised diphosphatidylglycerol, phosphatidylmono methyl ethanolamine (PME), phosphatidylethanolamine (PE), hydroxy-PME (OH-PME), hydroxy PE (OH-PEE), phosphatidylglycerol (PG), ninhydrin-positive phosphoglycolipid and unknown phospholipid, fatty acids with major amounts of i-C-16:0, ai-C-15:0 and ai-C-17:0 supported allocation of the strain to the genus Nonomuraea. Results of DNA-DNA hybridization and physiological tests allowed genotypic and phenotypic differentiation of strain DRQ-2(T) from closely related species. The genomic DNA G+C content of the organism was 72.5 mol%. On the basis of phenotypic, chemotypic and molecular characteristics, strain DRQ-2(T) represents a novel species of the genus Nonomuraea, for which the name N. indica sp. nov. is proposed, with type strain DRQ-2(T) (= NCIM 5480(T) = CCTCC AA 209050(T)).

Vitellibacter nionensis sp nov., isolated from a shallow water hydrothermal vent - Rajasabapathy, Raju; Mohandass, Chellandi; Yoon, Jung-Hoon; Dastager, Syed Gulam; Liu, Qing; Thi-Nhan Khieu; Chu Ky Son; Li, Wen-Jun; Colaco, Ana (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel, Gram-stain-negative, non-motile, rod-shaped yellow bacterium, designated VBW088(T) was isolated from a shallow water hydrothermal vent in Espalamaca in the Azores. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain VBW088(T) clustered with three type strains of species of the genus Vitellibacter and exhibited a sequence similarity of 97.3% with Vitellibacter soesokkakensis RSSK-12(T). However, strain VBW088(T) and V. soesokkakensis RSSK-12(T) exhibited low DNA-DNA relatedness (12.7 +/- 3.5 %). Strain VBW088(T) was positive for catalase and oxidase. Growth occurred at 10-37 degrees C, with the optimum at 80 degrees C, and at pH 6.0-8.0 (optimum pH 6.0) and in up to 5% (w/v) NaCl with optimum growth at 1-2% (w/v) NaCl. The major fatty acids (>10%) were iso-C-15:0 (33.5%) and iso-C-17:0 3-OH (32.0%). The polar lipids detected in strain VBW088(T) consisted of phosphatidylethanolamine, one unidentified aminolipid and three unidentified phospholipids. The DNA G+C content of strain VBW088(T) was 36.7 mol%. On the basis of phylogenetic inference, DNA-DNA relatedness, chemotaxonomic analysis and physiological data, the isolate represents a novel species of the genus Vitellibacter, for which the name Vitellibacter nionensis sp. nov. is proposed, with the type strain as VBW088(T). (=KCTC 32420(T)=MCC 2354(T)).

Actinorectispora indica gen. nov., sp nov isolated from soil, a member of the family pseudonocardiaceae - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Al Ruwaili, Jamal; Hozzein, Wael N.; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2016)
The taxonomic positions of three Gram-stain-positive, aerobic strains, designated YIM 75722, 75726 and 75728(T), and isolated from a soil sample collected from Kurnool of Andhra Pradesh province, India, were assessed using a polyphasic approach. Growth was observed at pH 7.0-10.0 (optimum pH 7.0), 15-28 degrees C (optimum 28 degrees C) and 0-8% (w/v) NaCl (grew without NaCl). Strains showed cylindrical spores with straight-chain morphology on aerial mycelium, but did not reveal sporangium-like structures or fragmentation of the substrate mycelium. Whole-cell hydrolysates of all strains contained galactose and ribose as the diagnostic sugars and meso-diaminopimelic acid as the diamino acid. The predominant menaquinone was MK-9(H-4); MK-9 (H-6) and MK-10 (H-4) were present in smaller amounts. The phospholipid pattern consisted mainly of diphosphatidylglycerol, phosphatidylglycerol and phosphatidylcholine. The major fatty acids were i-C-15: 0, ai-C-15: 0, i-C-17 : 0 and ai-C-17 : 0. The genomic DNA G+C content was 68.0 mol%. Phylogenetic analysis, based on 16S rRNA gene sequences, revealed that strain YIM 75728(T) should be placed within the family Pseudonocardiaceae, in which the strain formed a distinct lineage. The combination of phylogenetic analysis, phenotypic characteristics and chemotaxonomic data support the conclusion that strain YIM 75728(T) represents a novel species of a novel genus of the family Pseudonocardiaceae for which the name Actinorectispora indica gen. nov., sp. nov., is proposed. Strain YIM 75728(T) (=DSM 45410(T)=CCTCC AA 209065(T)) is the type strain of Actinorectispora indica. Strain YIM 75728(T) was considered as the type strain over the other two strains based on the highest sequence read length of the strain.

Editorial: actinobacteria in special and extreme habitats: diversity, function roles, and environmental adaptations - Qin, Sheng; Li, Wen-Jun; Dastager, Syed Gulam; Hozzein, Wael N. (Frontiers in Microbiology, 2016)
Keywords: actinobacteria; activities; diversity; environmental adaptation; omics technologies; special and extreme environments

Streptomyces lonarensis sp nov., isolated from lonar lake, a meteorite salt water lake in India - Sharma, Trupti K.; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Shinde, Vidhya K.; Zhan, Jing; Li, Wen-Jun; Rele, Meenakshi V.; Dastager, Syed Gulam; Kumar, Lalitha Sunil (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2016)
A novel alkaliphilic actinomycete, strain NCL716(T), was isolated from a soil sample collected from the vicinity of Lonar Lake, an alkaline salt water meteorite lake in Buldhana district of Maharashtra State in India. The strain was characterised using a polyphasic taxonomic approach which confirmed that it belongs to the genus Streptomyces. Growth was observed over a pH range of 7-11 at 28 A degrees C. The cell wall was found to contain ll-diaminopimelic acid and traces of meso-diaminopimelic acid. The major fatty acid components were identified as iso-C-16:0 (46.8 %), C-17:1 (12.4 %), anteiso-C-15:0 (5.1 %) and anteiso-C-17:1 (4.8 %). The major polar lipids were identified as diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and phosphatidylinositol. The major menaquinones were determined to be MK-9 (H-6) (70.3 %), MK-9 (H-4) (15.5 %) and MK-9 (H-8) (7.2 %). The G+C content of the DNA of the type strain was determined to be 71.4 mol %. The 16S rRNA gene sequence has been deposited in GenBank with accession number FJ919811. Although the 16S rRNA gene sequence analysis revealed that strain NCL716(T) shares > 99 % similarity with that of Streptomyces bohaiensis strain 11A07(T), DNA-DNA hybridization revealed only 33.2 +/- A 3.0 % relatedness between them. Moreover, these two strains can be readily distinguished by some distinct phenotypic characteristics. Hence, on the basis of phenotypic and genetic analyses, it is proposed that strain NCL716(T) represents a novel species of the genus Streptomyces, for which the name Streptomyces lonarensis sp. nov., is proposed. The type strain is NCL 716(T) (=DSM 42084(T) = MTCC 11708(T) = KCTC 39684(T)).
Keywords: Alkaliphile; DDH analysis; Polyphasic taxonomy; Streptomyces lonarensis sp nov.

Kocuria indica sp. nov., isolated from a sediment sample (vol 64, pg 869, 2014) - Dastager, Syed G.; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Lee, Jae-Chan; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2017)